The John MI. Knutson Distinguished Service Award in Dental Public Health-2001 Recipient Robert E. Mecklenburg - Dushanka V. Kleinman, DDS, MScD (Blackwell Synergy, 2002)
I am honored to have the opportunity on this special occasion to say a few words about our 2001 Knutson Awardee this evening, Robert Ellis Mecklenburg. Admiral Mecklenburg, please allow me to call you "Meck."